Peran Pendidikan Agama Islam dalam Meningkatkan Kesehatan Mental dan Spiritual Peserta Didik - Yunitasari Yunitasari; Taher Afandi; Sofiatul Jannah (FKIP UNSULTRA, 2025)
Mental and spiritual health are two important aspects of student development that directly influence academic ability, emotional well-being, and character formation. Islamic Religious Education (PAI) plays a strategic role in strengthening these two aspects through the internalization of the values ​​of faith, piety, noble character, and self-control. This literature study aims to analyze the role of PAI in improving students' mental and spiritual health based on conceptual and empirical findings from various previous studies. The research method used a literature review approach by examining books, national and international journals, and relevant research reports. The analysis results indicate that PAI plays a significant role in improving mental health by strengthening emotional regulation, forming positive mindsets, reducing stress, and instilling resilience. Furthermore, PAI also strengthens the spiritual dimension through the appreciation of worship, the habit of dhikr (remembrance of God), self-reflection, and the integration of religious values ​​into daily behavior. The research findings indicate that students who receive effective PAI learning tend to be better at coping with academic pressure, building healthy social interactions, and demonstrating prosocial behavior. This study confirms that Islamic Religious Education (PAI) not only functions as a cognitive subject but also plays a significant role in developing students' mental and spiritual well-being as part of a holistic education. Therefore, more innovative, humanistic, and character-oriented PAI learning strategies are needed.